Viviendas en renta en ciudades mexicanas - Sobrino, Jaime (El Colegio de México A.C., 2020)
The purpose of this article is to study the number, evolution, characteristics, and territorial distribution of rental housing in Mexico and its main cities, as well as the sociodemographic attributes of the people and households that reside in them. The question that guides the article is the following: What has been the importance of rental housing in the country’s housing demand in the period 1950-2015, and how has rental housing been related to the more general processes of the city, such as poverty, inequality and segregation? To achieve these aims, the information on housing ownership contained in the population and housing censuses from 1950 to 2010 and the Intercensal Survey 2015 is used. The analysis focuses on the 95 cities with the largest population size in 2010. The main findings include the fact that the dynamism of rental housing in Mexico has not been significant, largely due to the housing policy established by the Mexican state, which has prioritized home ownership. The rental housing market is limited to specific cities and certain areas within cities, especially buildings and neighborhoods located in central areas. The proportion of houses for rent is related to the demographic dynamics of the city, the larger number of one-person households, the higher population density, its specialization in tourist activities and greater social inequality. There is also a close relationship between the life course of individuals, the cycle of families and the type of ownership in their residential selection.